IMPACTS OF GREEN TRAINING ON THE PERFORMANCE OF LOGISTICS COPMANIES - Chuyen, Doan Thi (PEOPLE: International Journal of Social Sciences, 2024)
This paper explores the effects of green training, green intellectual capital, and green logistics practices on the performance and sustainability of logistics enterprises, focusing on firms in Ho Chi Minh City, Vietnam. A quantitative methodology, including Structural Equation Modeling (SEM), was applied to analyze data from 437 respondents representing logistics firms. The results affirm that green training enhances employees’ environmental skills and awareness, leading to improved operational efficiency and reduced ecological impact. Green intellectual capital supports innovation, fostering long-term competitive advantages, while green logistics practices streamline processes, lower costs, and enhance sustainability. These findings contribute to the broader understanding of sustainable development by emphasizing the strategic importance of green practices in achieving economic and environmental goals within the logistics industry. The study offers actionable insights for policymakers and industry leaders aiming to integrate sustainability into organizational frameworks.